Research of a New Non-Layer Protocol Architecture for Satellite Network - Lixiang Liu; Dapeng Wang; Lu Wang (Institute of Advanced Engineering and Science, 2014)
The traditional hierarchical network architecture has the defect of redundancy and no interaction between the layers. These defects have bad impact on QoS and network security. Hierarchical network protocols are difficult to be used to satellite network. This paper analysis the different network protocol architecture and propose a new network protocol architecture for satellite-Component-based network architecture, this architecture is proposed for eliminating of hierarchical network design flaws. Network protocols will be divided according to the function for forming of low coupling functional components. It provides high quality services to the application using combined components. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5448